Parameters influencing FVIII pharmacokinetics in patients with severe and moderate haemophilia A. (13th January 2015) - Kepa, S.; Horvath, B.; Reitter‐Pfoertner, S.; Schemper, M.; Quehenberger, P.; Grundbichler, M.; Heistinger, M.; Neumeister, P.; Mannhalter, C.; Pabinger, I.
Summary In haemophilia A patients factor VIII (FVIII) recovery and half‐life can vary substantially. There are parameters known to modulate FVIII pharmacokinetics (PK), but they explain only about 34% of the variability. The aim of this study was to identify new parameters that influence FVIII PK and thus to expand the current knowledge. FVIII PK were determined in 42 haemophilia A patients (37 severe, 5 moderate) without inhibitor. Patients' characteristics and laboratory parameters were evaluated for an association with FVIII PK. We analysed plasma levels of low‐density lipoprotein receptor‐related protein 1 (LRP1) and protein C (PC) activity, which had been hypothesized to influence FVIII activity. Furthermore, four variations in intron 6 of the LRP1 gene, which had been shown to influence LRP1, were investigated. FVIII half‐life differed widely from 6.2 to 20.7 h, with a median of 10.0 h. Patients with blood group O had shorter FVIII half‐life compared to patients with non‐O blood group (median FVIII half‐life 9.0 h vs. 10.4 h, P = 0.018). Age was significantly associated with FVIII half‐life (r = 0.32, P = 0.035). Besides age, also VWF antigen (r = 0.52, P < 0.001) and blood group (r = −0.37, P = 0.015) was associated with FVIII half‐life. No correlation was found with FVIII‐ or LRP1‐genotype, LRP1 or PC concentrations. Our data showed large differences in FVIII PK between individual patients and revealed age, blood group and VWF levels as important determining factors for FVIII half‐life. FVIII genotype or levels of LRP1 or PC had no influence on FVIII PK.